Regulación emocional en estudiantes de educación primaria Institución Educativa N° 61008, Iquitos 2022 - Flores Ochoa, Llisely Mayte (2023)
The study has the following title; Emotional regulation in primary education students’ educational institution No. 61008 Iquitos2022; As a general objective, to compare the levels of emotional regulation according to gender in the primary education students of the Educational Institution No. 61008 of the Iquitos 2022 district. The elements of the methodology were the type of research, non-experimental, with a Comparative Descriptive design. transactional, with a sample of 141 students from the first to the sixth grade of primary school; the technique used was the survey and the instrument was a questionnaire to collect data on Emotional Regulation. The results in general of the level of emotional regulation according to gender of primary school students, these indicate frequencies in women of low regulation in 1.3% and in men of 9.2%. In the average regulation, a higher percentage is observed in women with 89.5% and in men with 81.5%.But in the regulation the same percentage is observed 9.2% in women and in men respectively. The averages were also higher in women of 43.92 points compared to men, which was 42.07 points, observing a similar standard deviation between them. Using the test statistician: Mann-Whitney U, Mann-Whitney U statistical value = 1795.5, p-value 0.005; It is concluded that the levels of emotional regulation are different according to the gender of the primary education students of the Educational Institution No. 61008 of the Iquitos 2022 district. (p=0.005 < ? = 0.05), the Ho is rejected and the Ha hypothesis is accepted. at a significance level of 0.05%.